Perancangan UI/UX E- KTM Multifungsi Berbasis Digital Menggunakan Metode Prototype: Studi Kasus : KTM Universitas Trunojoyo Madura - Tazkiyatul W; Ramadani F; Bilal R; Yasid F; Siti Nur H; Prita Dellia (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The advancement of digital technology has driven the transformation of conventional student ID cards (KTM) into digital-based cards with various additional functions. This study aims to design the user interface (UI) and user experience (UX) of a digital-based multifunctional e-KTM at Trunojoyo University, Madura using the prototype method. This method was chosen because it allows rapid design iteration based on user feedback. This e-KTM is expected to not only function as a student identity, but can also be used for library access, attendance, payments, and other academic services. The design process involves needs analysis, initial design creation, user testing, and improvements based on evaluation results. The results of the study show that the application of the prototype method improves the quality of UI/UX design by better meeting user needs. With this multifunctional e-KTM, it is hoped that the efficiency of campus services will increase and provide a more practical experience for students.